Shared ancestral polymorphisms and chromosomal rearrangements as potential drivers of local adaptation in a marine fish - Hugo Cayuela; Quentin Rougemont; Martin Laporte; Claire Mérot; Eric Normandeau; Yann Dorant; Ole K. Tørresen; Siv Nam Khang Hoff; Sissel Jentoft; Pascal Sirois; Martin Castonguay; Teunis Jansen; et al. (Molecular Ecology, 2020)
Gene flow has tremendous importance for local adaptation, by influencing the fate of de novo mutations, maintaining standing genetic variation and driving adaptive introgression. Furthermore, structural variation as chromosomal rearrangements may facilitate adaptation despite high gene flow. However, our understanding of the evolutionary mechanisms impending or favouring local adaptation in the presence of gene flow is still limited to a restricted number of study systems. In this study, we examined how demographic history, shared ancestral polymorphism, and gene flow among glacial lineages contribute to local adaptation to sea conditions in a marine fish, the capelin ( Mallotus villosus ). We first assembled a 490‐Mbp draft genome of M. villosus to map our RAD sequence reads. Then, we used a large data set of genome‐wide single nucleotide polymorphisms (25,904 filtered SNPs) genotyped in 1,310 individuals collected from 31 spawning sites in the northwest Atlantic. We reconstructed the history of divergence among three glacial lineages and showed that they probably diverged from 3.8 to 1.8 million years ago and experienced secondary contacts. Within each lineage, our analyses provided evidence for large N e and high gene flow among spawning sites. Within the Northwest Atlantic lineage, we detected a polymorphic chromosomal rearrangement leading to the occurrence of three haplogroups. Genotype–environment associations revealed molecular signatures of local adaptation to environmental conditions prevailing at spawning sites. Our study also suggests that both shared polymorphisms among lineages, resulting from standing genetic variation or introgression, and chromosomal rearrangements may contribute to local adaptation in the presence of high gene flow.

Polygenic selection drives the evolution of convergent transcriptomic landscapes across continents within a Nearctic sister species complex - Clément Rougeux; Pierre‐Alexandre Gagnaire; Kim Praebel; Ole Seehausen; Louis Bernatchez (Molecular Ecology, 2019)
In contrast to the plethora of studies focusing on the genomic basis of adaptive phenotypic divergence, the role of gene expression during speciation has been much less investigated and consequently less understood. Yet, the convergence of differential gene expression patterns between closely related species‐pairs might reflect the role of natural selection during the process of ecological speciation. Here, we test for intercontinental convergence in differential transcriptional signatures between limnetic and benthic sympatric species‐pairs of Lake Whitefish ( Coregonus clupeaformis ) and its sister lineage, the European Whitefish ( Coregonus lavaretus ), using six replicated sympatric species‐pairs (two in North America, two in Norway and two in Switzerland). We characterized both sequence variation in transcribed regions and differential gene expression between sympatric limnetic and benthic species across regions and continents. Our first finding was that differentially expressed genes (DEG) between limnetic and benthic whitefish tend to be enriched in shared polymorphism among sister lineages. We then used both genotypes and covariation in expression in order to infer polygenic selection at the gene level. We identified parallel outliers and DEG involving genes primarily overexpressed in limnetic species relative to the benthic species. Our analysis finally revealed the existence of shared genomic bases underlying parallel differential expression across replicated species‐pairs from both continents, such as a cis ‐eQTL affecting the pyruvate kinase expression level involved in glycolysis. Our results are consistent with a long‐standing role of natural selection in maintaining trans‐continental diversity at phenotypic traits involved in ecological speciation between limnetic and benthic whitefishes.

Microsatellite loci for genetic analysis of the arctic gadids Boreogadus saida and Arctogadus glacialis - R. John Nelson; Caroline Bouchard; Matias Madsen; Kim Praebel; Eric Rondeau; Kristian von Schalburg; Jong S. Leong; Stuart Jantzen; Zoe Sandwith; Stephanie Puckett; Amber Messmer; Svein-Erik Fevolden; et al. (Conservation Genetics Resources, 2013)